Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{7}{2}\times\dfrac{3}{4}+\dfrac{17}{8}\times\dfrac{2}{3}+\dfrac{3}{4}\times\dfrac{1}{2}+\dfrac{7}{8}\times\dfrac{3}{3}\)
\(=\dfrac{7\times3}{2\times4}+\dfrac{17\times2}{8\times3}+\dfrac{3\times1}{4\times2}+\dfrac{7}{8}\times1\)
\(=\dfrac{21}{8}+\dfrac{17}{12}+\dfrac{3}{8}+\dfrac{7}{8}\)
\(=\left(\dfrac{21}{8}+\dfrac{3}{8}+\dfrac{7}{8}\right)+\dfrac{17}{12}\)
\(=\dfrac{31}{8}+\dfrac{17}{12}\)
\(=\dfrac{31\times3}{8\times3}+\dfrac{17\times2}{12\times2}\)
\(=\dfrac{93}{24}+\dfrac{34}{24}\)
\(=\dfrac{127}{24}\)
[4\(\dfrac{1}{5}\) - 2\(\dfrac{2}{5}\)] x 8\(\dfrac{5}{6}\)
= [\(\dfrac{21}{5}\) - \(\dfrac{12}{5}\)] x \(\dfrac{53}{6}\)
= \(\dfrac{9}{5}\) x \(\dfrac{53}{6}\)
= \(\dfrac{159}{10}\)
[5\(\dfrac{1}{3}\) - 2\(\dfrac{2}{3}\)]: \(\dfrac{3}{7}\)
= [\(\dfrac{16}{3}\) - \(\dfrac{8}{3}\)]: \(\dfrac{3}{7}\)
= \(\dfrac{8}{3}\) : \(\dfrac{3}{7}\)
= \(\dfrac{56}{9}\)
=5/4x4/3=5/3
=5/4:3/4=5/3